Model Pengembangan Pariwisata Berkelanjutan dan Konsekuensi Ekonominya bagi Masyarakat Pringsewu: Sebuah Analisis Etika Bisnis Islam - Siti Rohaya (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
The development of the tourism sector plays a significant role in enhancing community economic welfare while contributing to regional and national income. In Pringsewu Regency, tourism potential is utilized to support regional development and to shape the distinct identity of the area. As a sector that directly interacts with local communities, tourism generates various social and economic impacts on the surrounding population. This study aims to analyze the strategies used in developing the tourism industry and to examine its impacts on the community’s economy from the perspective of Islamic business ethics. This research employs a qualitative approach with a field research design, descriptive in nature, and collects data through interviews and documentation. The data were analyzed inductively to obtain a comprehensive understanding of the phenomenon. The findings indicate that the tourism development strategies implemented by the Pringsewu Regency Government include conducting tourism awareness training and outreach programs, promoting tourism through social and electronic media, organizing various events, and improving supporting facilities and infrastructure. The economic impacts of tourism on the community are reflected in increased income levels, the creation of employment and entrepreneurial opportunities, and the growing involvement of women in economic activities. From the perspective of Islamic business ethics, these strategies and their implementation align with the principles of trustworthy resource management, responsible utilization of natural assets, and environmental preservation, all of which represent ethical values emphasized in Islam.